Prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from chromosome 2 - Chih-Ping Chen; Ming Chen; Shun-Ping Chang; Fang-Yu Hung; Meng-Ju Lee; Schu-Rern Chern; Peih-Shan Wu; Yen-Ni Chen; Shin-Wen Chen; Chen-Chi Lee; Dai-Dyi Town; Wen-Lin Chen; et al. (Elsevier, 2017)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome (sSMC) derived from chromosome 2. Case Report: A 42-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XY,+mar[10]/46,XY[12]. The parental karyotypes were normal. Array comparative genomic hybridization analysis of the DNA extracted from cultured amniocytes revealed no genomic imbalance. Spectral karyotyping analysis failed to identify the sSMC. Metaphase fluorescence in situ hybridization analysis using the satellite probes CEP1/5/19, CEP2, CEP3, CEP4, CEP6, CEP7, CEP8, CEP9, CEP10, CEP12, CEP13/21, CEP14/22, CEP15, CEP16, and CEP20 revealed a result of 47,XY,+mar .ish der(2)(D2Z+)[10]. The sSMC was derived from the α satellite of chromosome 2. Polymorphic DNA marker analysis using the markers specific for chromosome 2 on the DNAs extracted from cultured amniocytes and parental bloods excluded uniparental disomy 2. At 39 weeks of gestation, a healthy 3394-g male baby was delivered with no phenotypic abnormality. The cord blood had a karyotype of 47,XY,+mar[21]/46,XY[19]. Conclusion: Array comparative genomic hybridization and spectral karyotyping may fail to detect an sSMC derived from α satellite, which needs satellite probes for confirmation.